A Smart IoT-based Automated Irrigation for Farms Using Node MCU (ESP 32F ESP8266 MC) and A Humidity Sensor - Alsammak , Hayder Nasser; Mohammed , Ziad Saeed (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Agriculture is one of the most important sectors of production in Iraq. Centralised agriculture suffers from a critical problem with regard to the provision of water. In this paper, an automated irrigation system, which could be operated automatically without human intervention, was developed using Internet technology to help farmers maintain soil moisture. Where many commands could be found to control parts of this system. Several controllers were connected to sensors, and the data were converted from one type to another while being transmitted from a wireless Wi-Fi to a wired transmission via a Blynk server that worked with the system. Therefore, the system was designed to achieve all the goals related to the use of water: reduction of labour, energy consumption, productivity, and rationing of the heavy utilization of water while maintaining soil moisture levels by relying on constant agricultural activities for each field. The work was carried out in a greenhouse, where a crop of cherry tomatoes was grown, and comparisons were then made to a field irrigated by the usual method. The results showed a saving of 48% in the use of water compared to the traditional method and an increase in the plant vegetative growth and productivity.